PERAN NINIK MAMAK DALAM PEMANFAATAN TANAH ULAYAT DI KENAGARIAN LIPAT KAIN SELATAN - Rifana, Rinda; Bachtiar, Maryati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Customary law is part of the law that comes customs, the social norms are created and maintained by the functionalist law and apply and are intended to regulate legal relations in society. Customary law governs the indigenous people and their customary land. Legal relationship between indigenous people and land creates the right that gives the community as a group of law, the right to use the land for the benefit of society. Each has the customary rights of indigenous peoples. Customary rights is the right of communion law to use freely the lands which remained a grove within the region, for the benefit of the fellowship of the law itself and its members, or to the interests of those outcomes (foreigners or immigrants), with the permission of the legal communion with pay beyond that (recognition).Talking about customary land, customary land rights holders led by traditional authorities or the prince of the tribe. Article 9 of Regional Regulation (Perda) of Kampar regency No. 12 of 1999 concering about customary land rights states thats, the prince of the tribe task is to govern, prosperity, and security in their respective alliances in the field of customs law. That mean is, the prince of the tribe obliged to maintain the welfare and interests of community members in order to avoid disputes.Key Words: Role - Ninik Mamak - Utilization - Communal Land